KARAKTERISTIK LALU LINTAS DI SEPANJANG PINGGIRAN KOTA PONTIANAK TANPA MEDIAN JALAN ( JALAN SUNGAI RAYA DALAM ) - januardi, Hendri; Erwan, Komala; Kadarini, Siti Nurlaily (Jurnal Mahasiswa Teknik Sipil Universitas Tanjungpura, 2018)
Road Of Sungai Raya Dalam serves as a collector road for two-way trafficand serve a mixed traffic ie continuous traffic.and local traffic by vehicle type likes : heavy vehicles, light vehicles, motor vehicles and unmotorized vehicles. Given the preparation of the Indonesia Road Capacity Manual 1997( HCM ) â€œHIGHWAY CAPACITY MANUAL PROJECTâ€ is based on limited data especially for urban roads, Road Of Sungai Raya Dalam is located in the southeastern city of Pontianak with total population is of Â± 59.809,00. which belong to the middle class. So the traffic behavior of course has a variety of characters and different from other big cities that exist in Indonesia. Therefore the research conducted by the author aims to find out how the adjustment should be done on the results of the countMKJI-1997 ( HCM ) for Pontianak, Road Of Sungai Raya DalamÂ  network located in a medium city by analyzing traffic characteristics.In the analysis of the characteristics of the Sungai Raya Dalam Highway, a period of observation per / 15 minutes per hour is observed and through several stages of calculation, among others; data volume (flow), space mean speed and vehicle density (density).Based on the optimum speed and density review, the model is based on field data in accordance with the Indonesian Road Capacity Manual 1997 ( HCM ) and field results describe the characteristics for the Sungai Raya Dalam road traffic. Based on the result of MKJI-1997 calculation is obtained the adjustment of road capacity between 1.08 - 1.99.Â Keywords: collector road, MKJI-1997, relation speed, volume, density and road capacity